Pengaruh Penerapan Prinsip-Prinsip Good Government Governance terhadap Kinerja Pegawai Bidang Keuangan: (Studi pada Pemerintah Daerah Kota Bandar Lampung) - Ashabul Maimanah; Nurdiono Nurdiono (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
The background to this research was to determine the effect of implementing the principles of good government governance on the performance of employees in the financial sector. The study was conducted at the Regional Government of Bandar Lampung City. The research approach used in this research is a quantitative approach. The data source for this research is respondent data obtained directly based on a questionnaire. The results of data analysis show that the application of good government governance principles has an effect on the performance of financial sector employees.